Peningkatan Keterampilan Membaca Pemahaman Menggunakan Metode Discovery Learning Berbantuan Media Komik Strip - Dadang Suhada; Nuratikah Nuratikah (Journal on Education, 2024)
The purpose of this study is to improvereading comprehension Skills by using the discovery learning method with the aid of comic strip media in the fourth grade students of MI Hidayatussibyan, Krangkeng sub-districk, Indramayu districk.By counducting classroom action research, it is hoped that it will be useful for various parties related to learning activities, especially Indonesia language lessons, including: teachers, students, community scools and the word of education.This typeof research is classroom action research which is carried out in two cycles, each cycle consisting of stages of planning, action observation, and reflection. This research was counducted at MI Hidayatussibyan for the academic year 2021 in 2022, the subjects who will be subject to action are fourth grade students with a total sample of 28 students, the aducational instrumen usedare observation and communication methods.